Re: Effect of Sacral Neuromodulation on Female Sexual Function and Quality of Life: Are They Correlated? - Mai Banakhar; Yahya Gazwani; Mohamed El Kelini (Journal of Urological Surgery, 2015)
Sacral neuromodulation (SNM) has become an established therapy for voiding dysfunction (VD). There have been published papers that documented improvement in bowel functions and bladder pain via SNM. However, improvement in female sexual function (FSF) after SNM treatment remains unclear. Recently, Banakhar et al. evaluated the effects of SNM on FSF and its impact on quality of life (QoL) and analyzed any correlation. They evaluated 33 female patients who were treated with SNM for VD. All patients completed the Female Sexual Function Index (FSFI), the 36-Item Short-Form Health Survey (SF-36), and incontinence questionnaires (the Urinary Distress Inventory [UDI-6]) preoperatively and 4 months postoperatively. Ten patients were excluded from the study because they were not sexually active. The indications were: refractory overactive bladder in 19, frequency urgency syndrome in 2, and non-obstructive urinary retention in another 2 patients. SNM therapy significantly improved the total FSFI score (p=0.011). When the SF-36 and UDI-6 scores were compared, QoL showed significant improvement after SNM treatment. However, improvement in FSFI scores was not correlated with improvement in QoL. SNM therapy is an effective treatment modality in selected patient groups. In our country, SNM therapy has become a new option in the treatment of lower urinary tract problems. According to the results of this study, it is too early to conclude that SNM certainly improve FSF and QoL. The study just evaluated 23 cases. In order to have a more discrete conclusion, we need prospective trials with larger series